(3GdQMeI dcKjQ ef GdCfGe aj eYQaI TF ef CMcGe GdMdGd hGdMQGes - (3eMeO GdYdejs
(3ChdgG (B:s
(3MeOkG def aJM CHhGH GdYfGjI dCQHGH GdgOGjI s
(3BNQgG (B:s
(3hbGd JYGdi (B: (3jNJU HQMeJg ef jTGA hGddg Ph GdaVd GdYXje hGddg GYde JeJ HMeOg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHY hGdYTQhfs
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ ESMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs